Ilmu Pengetahuan Alam dan Bidang 4 Ilmu Pengetahuan Alam - Ayu Arina Putri; Intan Arinda Sabilla; Siti Afifah Fadhilah; Viki Aridansyah; Muhammad Farras Qoid Mufadhol; Wati Sukmawati (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
Natural Sciences (IPA) are the knowledge of nature, including living things, dead objects, and processes that occur around it. Natural science is a branch of science that is very broad and includes physics, chemistry, biology, and the science of Earth and Space. This study aims to explore the importance of natural science (IPA) in basic education, focusing on developing scientific skills and understanding of natural phenomena. The method used in this study is descriptive qualitative. This approach aims to describe the phenomena that occur in science learning and analyze their effectiveness in increasing student understanding. The results showed that IPA learning has an important role in student daily lives. With an interdisciplinary approach that includes physics, chemistry, biology, and earth and space science, from the four IPA fields allow students to develop critical thinking skills and problem solving needed to face global challenges. Thus, natural science is very important in everyday life and also in understanding the relationship between humans and nature. Through a deep understanding of natural science, we can better appreciate the beauty of nature and play an active role in maintaining its sustainability for future generations.